Description of drought management actions [Part 1. Components of drought planning. 1.3. Methodological component] - Moneo M.; Iglesias A. (Drought management guidelines technical annex, 2007)
This chapter presents a compendium of drought management actions related to agriculture and water supply systems together with a common conceptual framework based on the use of drought indicators for evaluating the levels of drought risk (pre-alarm, alarm, and emergency), that allow establishing linkages between science and policy. The rationale is that the actions relevant to all sectors are derived based in common institutional organization, legal framework, and are implemented by a unique decision making structure (defined in the organizational component of the Guidelines).